2007
DOI: 10.1177/0265407507075410
|View full text |Cite
|
Sign up to set email alerts
|

Social comparison and satisfaction with one's social life

Abstract: In this study (N = 96), the role of social comparison in evaluating the quality of one's friendships and social relationships was examined. Participants who were exposed to a comparison target with a very dissatisfying social life evaluated their own social life as better than participants who were exposed to a comparison target with a very satisfying social life. However, this effect was only found among individuals high in the individual characteristic social comparison orientation. It is concluded that only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…This study is one of the few to demonstrate the importance of social comparison orientation for social relationships (Buunk et al, 2007) and, more specifically, for the similarity-attraction relationship (Michinov & Michinov, 2001). Our findings extend Michinov and Michinov's (2001) results which demonstrated that high-comparison orientation individuals are equally attracted to similar and dissimilar targets when they have not received any information about the group membership of the target.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This study is one of the few to demonstrate the importance of social comparison orientation for social relationships (Buunk et al, 2007) and, more specifically, for the similarity-attraction relationship (Michinov & Michinov, 2001). Our findings extend Michinov and Michinov's (2001) results which demonstrated that high-comparison orientation individuals are equally attracted to similar and dissimilar targets when they have not received any information about the group membership of the target.…”
Section: Discussionsupporting
confidence: 78%
“…Buunk and Gibbons (2006) pointed out that the consequences of social comparison information are more pronounced among high than low SCO individuals. Thus, high-SCO individuals seem to be more concerned with "being evaluated"than low-SCO individuals, and they can be affected differently by social comparisons (Buunk & Gibbons, 2006;Buunk et al, 2007). With regard to attitudes and opinions, Michinov and Michinov (2001) found that the similarity-attraction relationship did not appear among high-comparison orientation individuals.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Some people are more predisposed than others to rely on these comparisons. The impact of such individual differences is well documented in a variety of domains, such as satisfaction with social life, burnout among nurses and relationship satisfaction (Buunk, Groothof, & Siero, 2007;Buunk, Zurriaga, & Peíro, 2010;Dijkstra, Buunk, T oth, & Jager, 2007).…”
Section: Social Comparisons and Knowledge Awarenessmentioning
confidence: 99%